Phonon transport in Janus monolayer MoSSe: a first-principles study - Guo, San-Dong (Physical chemistry chemical physics : PCCP, 2018)
Transition Metal Dichalcogenide (TMD) monolayers are very widely studied due to their unique physical properties. Recently, Janus TMD monolayer MoSSe, with a sandwiched S-Mo-Se structure, has been synthesized by replacing the top S atomic layer in MoS 2 with Se atoms. In this work, we systematically investigate the phonon transport and lattice thermal conductivity ( κ L ) in MoSSe monolayers using first-principles calculations and the linearized phonon Boltzmann equation within the single-mode relaxation time approximation (RTA). The calculated results show that the κ L of MoSSe monolayers is much lower than that of MoS 2 monolayers, and higher than that of MoSe 2 monolayers. The corresponding thermal sheet conductance of MoSSe monolayers is 342.50 W K −1 at room temperature. This can be understood by studying the phonon group velocities and lifetimes. Compared to MoS 2 monolayers, the smaller group velocities and shorter phonon lifetimes of MoSSe monolayers give rise to a lower κ L . The larger group velocities of MoSSe compared to those of MoSe 2 monolayers are the main reason for the higher κ L . The elastic properties of MoS 2 , MoSSe and MoSe 2 monolayers are also calculated, and the order of the Young's modulus is identical to that of the κ L . The calculated results show that isotope scattering leads to a 5.8% reduction of the κ L . The size effects on the κ L are also considered, and are usually used in device implementation. When the characteristic length of the MoSSe monolayer is about 110 nm, the κ L reduces to half. These results may offer perspectives on thermal management of MoSSe monolayers, for applications in thermoelectrics, thermal circuits and nanoelectronics, and may motivate further theoretical or experimental efforts to investigate thermal transport in Janus TMD monolayers. First principles investigation of the phonon transport and lattice thermal conductivity ( κ L ) in MoSSe, MoS 2 and MoSe 2 monolayers.